Marine propulsion simulation (2014)
This work is the result of three years of research carried out between January 2010 and December 2012 as part of The XXV cycle Ph.D course in Naval Architecture and Marine Engineering. This course is provided by the “Ph.D. School in Science and Tech- nologies for Engineering” of the Università Degli Studi Di Genova (UNIGE). This work belongs to the Italian academic sector ING-IND/02 (Marine Construction & Marine Systems). Funding has been provided by a scholarship from the Regione Liguria. The challenge of this work is to develop a multi-physics simulation platform able to represent the dynamic behaviour of a ship in the time domain. With respect to pre- vious work available in literature, where the systems are often modeled one at a time, the aim is to merge into a unique platform three ship macro-systems that contribute to the global ship dynamics: the ship manoeuvrability, the ship propulsion plant, and the control system. In this way, it is possible to catch the mutual interaction between all the involved elements treating the ship as a whole. Design and optimization of the propulsion plant is a crucial task of the ship de- sign due to the fact that the global behaviour of a ship is greatly inuenced by the dynamic performance of the propulsion system. Dierent operational speeds, accel- eration, deceleration, crash stop, and heavy turning are some examples of transient situations that a propulsion system has to sustain without reducing ship safety and re- liability. These aspects become crucial issues if the ship is a naval vessel. The dynamic behaviour of the propulsion system is mainly aected by the control system perfor- mance, i.e., the capacity of the control system to properly use the power necessary to perform the required task within the boundary conditions imposed by machinery or environmental constraints. The main focus of this work is to develop and use the platform for the designs of the propulsion plant and the propulsion control system for a naval vessel in the early design stage. Using this platform, it is possible to develop the control system; to try new control logics; to choose the main engines; to test the control system under dierent operational conditions before the ship is built. In this way, the global design time could be reduced and the nal product could be better compared to the standard design technique. It also can reduce the time and cost of the sea trial for nal tuning. To reach this goal, the propulsion control logics have been rst developed in a vir- tual environment and then in a real PLC to increase result reliability. The PLCs, linked to the ship virtual model, has been thoroughly tested and optimized. This involves a set of technical problems. The crucial task is to develop a ship simulator able to run in real time, so particular attention has been dedicated to the choice and the develop- ment of system physical models and their computation time.